Antibiotic susceptibility of intestinal Escherichia coli in men undergoing transrectal prostate biopsies: a prospective, registered, multicentre study. (6th April 2018) - Knaapila, Juha; Kallio, Heini; Hakanen, Antti J; Syvänen, Kari; Ettala, Otto; Kähkönen, Esa; Lamminen, Tarja; Seppänen, Marjo; Jambor, Ivan; Rannikko, Antti; Riikonen, Jarno; Munukka, Eveliina; et al.
Abstract : Objectives: To determine, in a prospective, multicentre setting, the prevalence of fluoroquinolone‐resistant (FQ‐R) and extended‐spectrum β‐lactamase (ESBL)‐producing Escherichia coli ( E. coli ) strains in men undergoing transrectal ultrasonography‐guided prostate biopsy (TRUS‐Bx) in Finland; and to survey the associated risk factors for having the previously mentioned strains. Patients and Methods: This is a substudy of the trial investigating the role of magnetic resonance imaging (MRI) in prostate cancer diagnosis (Improved Prostate Cancer Diagnosis – Combination of Magnetic Resonance Imaging Targeted Biopsies and Biomarkers Multi‐institutional Study [multi‐IMPROD], NCT02241122). In all, 359 patients from four study centres were recruited to this prospective study. After having signed the informed consent form, these men with suspicion of prostate cancer completed a detailed questionnaire on their medical, smoking, and travelling history, as well as their recent use of antibiotics. After the bi‐parametric MRI scan, TRUS‐Bx was taken and a rectal swab sample was collected and cultured for determining the antimicrobial susceptibility profile of E. coli strains. The potential risk factors for having FQ‐R or third‐generation cephalosporin‐resistant (3GC‐R) E. coli strains were analysed using univariate and multivariate logistic regression analysis. Results: The percentage of FQ‐R and 3GC‐R E. coli strains amongst the study population was 13% and 8%, respectively. Amongst patients having E. coli strains, the rate of FQ‐R and 3GC‐R strains was 14% and 8%, respectively. Of the 3GC‐R E. coli strains, 62% proved to be ESBL‐producers and 88% were also FQ‐R. In multivariate analysis, international travel during the preceding year significantly increased the risk of having a FQ‐R E. coli strain (odds ratio [OR] 3.592, P = 0.001) and, unexpectedly, use of antibiotics during the previous year significantly decreased this risk (OR 0.442, P = 0.035). No significant risk factors for having 3GC‐R E. coli were identified. Conclusion: The occurrence of intestinal FQ‐R and/or 3GC‐R (potentially ESBL‐producing) E. coli strains in men undergoing TRUS‐Bx in Finland is notable. The finding is consistent with the global increase in antimicrobial resistance. International travel appears to be an indisputable risk factor for having intestinal FQ‐R E. coli strains. The contemporary antimicrobial resistance situation should be taken into account in the care of post‐TRUS‐Bx infections.